Frequency of Dysautonomia in Patients Presenting with Guillain-Barré Syndrome at Lady Reading Hospital, Peshawar - Zia Ullah; Zafar, Ayesha; Asad Ullah; Khan, Assadullah; Imad Ud Din (Indus Journal of Bioscience Research, 2025)
Background: Guillain-Barré Syndrome (GBS) is an acute immune-mediated polyneuropathy that often presents with variable clinical manifestations. Dysautonomia, a frequent but under-recognized complication, may significantly influence morbidity and mortality. The objective of this study was to determine the frequency of dysautonomia in patients with GBS and to explore its association with clinical characteristics and comorbidities. Methodology: A cross-sectional study was conducted on 112 patients diagnosed with GBS. Detailed demographic, clinical, and laboratory data were collected through structured proformas. Dysautonomia was assessed clinically and documented as present or absent. Variables such as age, gender, residence, duration of illness, GBS variants, preceding infection, comorbidities, and muscle power (MRC score) were analyzed. Data were entered into SPSS version 25. Chi-square test was applied to assess associations, with p < 0.05 considered statistically significant. Results: Dysautonomia was observed in 50% (56/112) of patients. Its occurrence was slightly higher among males (45.3%) compared to females (37.5%) and more frequent in patients above 40 years (39.3%). Dysautonomia was significantly associated with GBS variants, particularly AMAN (57.6%) compared to AIDP (35.4%). Preceding infections were also more frequent among patients with dysautonomia (53.6% vs. 41.9%), though the association was not statistically significant. No significant associations were found with age, gender, residence, comorbidities, or MRC scores. Conclusion: Dysautonomia is a common complication in GBS, particularly in AMAN variants. Early recognition and monitoring are essential to improve clinical outcomes.